Transcranioplasty Ultrasound Through a Sonolucent Cranial Implant Made of Polymethyl Methacrylate: Phantom Study Comparing Ultrasound, Computed Tomography, and Magnetic Resonance Imaging. Issue 7 (October 2019) - Belzberg, Micah; Shalom, Netanel Ben; Lu, Angela; Yuhanna, Edward; Manbachi, Amir; Tekes, Aylin; Huang, Judy; Brem, Henry; Gordon, Chad
Abstract : Background: Current methods of transcranial diagnostic ultrasound imaging are limited by the skull's acoustic properties. Craniotomy, craniectomy, and cranioplasty procedures present opportunities to circumvent these limitations by substituting autologous bone with synthetic cranial implants composed of sonolucent biomaterials. Objective: This study examined the potential to image the brain using transcranioplasty ultrasound (TCU) through a sonolucent cranial implant. Materials and Methods: A validated adult brain phantom was imaged using computed tomography (CT), magnetic resonance imaging (MRI), and ultrasound without an implant. Next, for experimental comparison, TCU was performed through a sonolucent implant composed of clear polymethyl methacrylate. Results: All imaging modalities successfully revealed elements of the brain phantom, including the bilateral ventricular system, the falx cerebri, and a deep hyperdense mass representing a brain tumor or hematoma. In addition, ultrasound images were captured which closely resembled axial images obtained with both CT and MRI. Conclusion: The results obtained in this first-ever, preclinical, phantom study suggest TCU is now a viable immediate and long-term diagnostic imaging modality deserving of further clinical investigation.